Turkmenistan – Rosja i „wieczysta neutralność” - Mironowicz, Eugeniusz (1955– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
After gaining independence in 1991, Turkmenistan’s domestic policy focused on eliminating foreign political and cultural infl uences. This approach effectively limited the presence of the Russian language and culture within the country. In terms of foreign policy, Turkmenistan’s economic ties necessitated cooperation with Russia. Nonetheless, the government withdrew from all organisations that integrated post-Soviet states. By the end of the 2000s, China emerged as Turkmenistan’s primary economic partner. However, by the end of the second decade, the authorities in Ashgabat, seeking to balance Chinese influence, decided to resume cooperation with Russia. Additionally, the involvement of the United States, the European Union, and India in the competition for access to energy resources in Central Asia, along with the Russian-Ukrainian conflict, significantly shaped the dynamics of Russian-Turkmen relations.
p. 231-249
Summary in English and Russian.
Keywords: Russia; Turkmenistan; neutrality; bilateral relations; gas; transport routes; Turkmenistan - politics and government - 1991-; gas - production and trade - Turkmenistan - 1990-; Turkmenistan - foreign economic relations - Russia - 1990-; Russia - foreign economic relations - Turkmenistan - 1990-